Animated 'worlds' - Buchan, Suzanne; Surman, David; Ward, Paul, 1968- (J. Libbey Pub., 2006)
"Animated Worlds is an edited compilation of the papers presented at the 'Animated 'Worlds'' conference held in 2003 at Farnham Castle, UK. What do we mean by the term 'animation' when we are discussing film? Is it a technique? - A style? - A way of seeing or experiencing 'a world' that has little relation to our own lived experience of 'the world'? The Animated 'Worlds' anthology presents a selection of topics from the 2003 Animated 'Worlds' conference held in England. Essays range from close film analyses to phenomenological and cognitive approaches, spectatorship, performance, literary theory and digital aesthetics that reveal the astonishing variety of 'worlds' animation confronts us with."--PUBLISHER